The Five Year Plan and Rural India June 1953 - (:unkn) unknown (Planning Commission, Government of India, 1953)
The 1953 Five-Year Plan by the Government of India presents a comprehensive strategy for transforming rural India, which constitutes over 70% of the nation’s population. The plan addresses critical challenges such as unemployment and underemployment in agriculture, fragmented landholdings, and dependence on monsoon rains. Key strategies include modernizing agricultural practices, expanding irrigation facilities, promoting cottage and small-scale industries, and strengthening cooperative structures. The plan emphasizes an integrated administrative framework linking state authorities and local leadership, ensuring effective knowledge transfer and community participation. A significant financial commitment underpins these initiatives, including investments in agricultural credit, irrigation, rural infrastructure, and famine relief. Additionally, reforms in land tenure aim to promote social justice and equitable resource access. By combining technological advancement, economic diversification, and public engagement, the plan seeks to enhance productivity, generate employment, and achieve socio-economic transformation, positioning rural development as central to India’s national progress and democratic stability.
Government of India, Planning Commission
Keywords: Five-Year Plan; Rural Development; Agriculture; Employment; Irrigation; Cottage Industries; Small-Scale Industries; Cooperative Societies; Land Reforms; Infrastructure; Public Participation; Socio-Economic Transformation